1972
DOI: 10.1039/p29720001831
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of nitroso-compounds. Part III. The nitrosation of substituted benzenes in concentrated acids

Abstract: Rates of nitrosation are reported for benzene, toluene, diphenyl ether, anisole, and phenol in 1 0 . 4 ~-H C J 0 , a t 52.9 "C, for benzene in 1 ~. ~M -H , S O , , and for [aH6]benzene in 1 2M-D2S0,. The effective reagent under these conditions is NO+ and substitution occurs predominantly a t the para-position of monosubstituted substrates. Benzene reacts about 50 times more rapidly in HzS04 than in HCIO, of the same Ho acidity, and about 8.5 times more rapidly than [2H6]benzene in D2S04, which shows that H+-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 0 publications
5
32
2
Order By: Relevance
“…The formation of the phosphine imide 11 and, particularly, the contrast between the formation of the benzimidazole 8 from 3, but of the benzimidazolone 9 from 4, were surprising. We had expected the reaction mechanism for the cyclisation of the nitroanilides 1 -4 to be similar to the one suggested for the cyclisation of 4-(acylamino)-5-nitrosopyrimidines [1], i.e., reduction of the NO 2 to the NO group, followed by addition of the phosphine to the NO group, and formation of an aza-Wittig reagent 5 ) via a nitrene or nitrenoid intermediate. Surprisingly, however, no intermediate phosphine imide was observed during the formation, under milder reaction conditions, of an 8-(tert-butyl)guanine from a 4-(pivaloylamino)-5-nitrosopyrimidine [1].…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The formation of the phosphine imide 11 and, particularly, the contrast between the formation of the benzimidazole 8 from 3, but of the benzimidazolone 9 from 4, were surprising. We had expected the reaction mechanism for the cyclisation of the nitroanilides 1 -4 to be similar to the one suggested for the cyclisation of 4-(acylamino)-5-nitrosopyrimidines [1], i.e., reduction of the NO 2 to the NO group, followed by addition of the phosphine to the NO group, and formation of an aza-Wittig reagent 5 ) via a nitrene or nitrenoid intermediate. Surprisingly, however, no intermediate phosphine imide was observed during the formation, under milder reaction conditions, of an 8-(tert-butyl)guanine from a 4-(pivaloylamino)-5-nitrosopyrimidine [1].…”
mentioning
confidence: 90%
“…Oxaziridine intermediates were considered before as intermediates in related reactions [42]. The NÀO bond of 19 may open either to generate the N-oxide 20 that will be deoxygenated by Ph 3 P, leading to the dimethylbenzimidazole 8, or to the orthodiazaquinoid intermediate 21 that will generate the rearranged product 9 either by a [1,5] sigmatropic rearrangement [43], or by a 1,2 pinacolÀpinacolone type migration of the i-Pr group. It is, however, not clear why there should be such a dichotomy in the opening of the oxaziridine substituted by either a Me, or an i-Pr group, so that one oxaziridine will react while maintaining the aromatic ring intact, and the other one lead to dearomatization.…”
mentioning
confidence: 99%
“…The nitrosonium ion NO ϩ being some 10 14 times less reactive than the nitronium ion NO 2 ϩ [1,2] much less attention has been paid to the C-nitrosation of aromatics than to their nitration, which is now well un-cursors of genotoxic substances, it is of some concern that phenol, catechol, vanillin, and other phenolics have been detected in smoked fish and meats [14]. It has also been reported that the presence of phenolic compounds can block the N-nitrosation reactions of other substrates [15,16], and although this has been questioned on the grounds that N-nitrosation is catalyzed by monohydroxy phenols [17] (but not by all polyhydroxyphenols [15]), it should be borne in mind that catalytic activity is only observed when the concentration of nitrosating agent significantly exceeds the concentration of phenol, which rarely occurs in vivo or in environmentally significant situations.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism implies the rate equation (4) The slow step in Scheme I is hypothesized, following Challis [1], to involve protonation of the nitroso oxygen in the transition state (Scheme II). Since this implies susceptibility to basic catalysis by organic bases, Schemes I and II are supported by the finding that, for phenol, k 2corr depends linearly on buffer concentration, …”
Section: Resultsmentioning
confidence: 99%